1995
DOI: 10.1007/s004410050523
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of amelogenesis in the rat lower incisor after thyro-parathyroidectomy, parathyroidectomy and thyroidectomy

Abstract: The effects of thyro-parathyroidectomy, parathyroidectomy or thyroidectomy upon enamel formation in the rat incisor were studied. One control group and four groups of surgically treated rats were used: parathyroid autotransplanted, thyroidectomized, parathyroidectomized, and thyro-parathyroidectomized. One month after surgery, the incisors were processed for light and electron microscopy. The present study revealed perturbations of the Tomes process morphology, of the rod pattern in the inner enamel formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This report shows that diet-induced hypocalcemia directly or indirectly results in major alterations of both the enamel organ and the enamel. The results are consistent with previous studies on experimentally induced chronic hypocalcemia suggesting that low calcium levels, rather than phosphate levels, cause enamel hypoplasia (Nikiforuk and Fraser 1979;Limeback et al 1992;Acevedo et al 1996). In the same experimental model as in the present study, it was previously found that diet-induced hypocalcemia results in hypocalcified enamel (Bonucci et al 1994).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This report shows that diet-induced hypocalcemia directly or indirectly results in major alterations of both the enamel organ and the enamel. The results are consistent with previous studies on experimentally induced chronic hypocalcemia suggesting that low calcium levels, rather than phosphate levels, cause enamel hypoplasia (Nikiforuk and Fraser 1979;Limeback et al 1992;Acevedo et al 1996). In the same experimental model as in the present study, it was previously found that diet-induced hypocalcemia results in hypocalcified enamel (Bonucci et al 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Complete absence of calcium in the diet results in the formation of hypomineralized enamel (Bonucci et al 1994). Furthermore, thyro-parathyroidectomy, which produces severe hypocalcemia, affects the morphology of ameloblasts as well as the organization and degree of mineralization of enamel (Acevedo et al 1996).…”
mentioning
confidence: 99%
“…(2) The cellular mechanisms that regulate the enamel maturation process are complex and poorly understood. Recent studies have shown that hypocalcemia either dietaryinduced (23,24) or experimentally induced (25) can cause enamel hypoplasia. Similarly, in vitro studies by Kukita and coworkers found that primary cultured rat ameloblasts responded to high concentrations of Ca 2ϩ in the medium by changing their morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about PTH is even more limited. Evidence from animal studies suggests that reduced levels of PTH induce hypocalcemia and consequently enamel alterations 17 .…”
Section: Introductionmentioning
confidence: 99%